Electroencephalogram Modifications Associated With Atypical Strict Antipsychotic Monotherapies. Issue 6 (December 2018) - Dias Alves, Manuel; Micoulaud-Franchi, Jean Arthur; Simon, Nicolas; Vion-Dury, Jean
Abstract: Background: Antipsychotics produce electroencephalogram (EEG) modifications and increase the risk of epileptic seizure. These modifications remain sparsely studied specifically for atypical antipsychotics. In this context, our study focuses on EEG modifications associated with atypical strict antipsychotic monotherapies. Methods: Electroencephalogram recordings of 84 psychiatric patients treated with atypical antipsychotics in strict monotherapy (clozapine, n = 22; aripiprazole, n = 22; olanzapine, n = 17; risperidone, n = 9; quetiapine, n = 8; risperidone long-acting injection, n = 4; and paliperidone long-acting injection, n = 2) were analyzed. The modifications were ranked according to both slowing and excitability scores. Results: Electroencephalogram modifications (in 51 subjects, 60.71%) were graded according to 4 stages combining general slowing and sharp slow waves and/or epileptiform activities. The presence of sharp or epileptiform activities was significantly greater for clozapine (90.9%) compared with other second-generation antipsychotics (aripiprazole, 50%; olanzapine, 58.8%; quetiapine, 37.5%; risperidone, 44.4%). Age, duration of disease progression, and diagnosis were not associated as risk factors. Electroencephalogram modifications were associated with lower doses for treatment with quetiapine but not for specific antipsychotics. Electroencephalogram modifications and severe excitability were associated with higher chlorpromazine equivalent doses. Conclusions: Atypical antipsychotics (clozapine, aripiprazole, quetiapine, olanzapine, and risperidone) induce EEG modifications, and these are significantly greater for clozapine and appear dependent on chlorpromazine equivalent dose. No encephalopathy was observed in these antipsychotic monotherapies, whatever dose.